Remdesivir modifies interferon response in hospitalized COVID-19 patients. Issue 5 (November 2022) - Murphy, Sarah L.; Halvorsen, Bente; Barratt-Due, Andreas; Dyrhol-Riise, Anne Ma; Aukrust, Pål; Trøseid, Marius; Dahl, Tuva B.
Highlights: Remdesivir downregulates interferon responses in hospitalized COVID-19 patients. Treatment had a particularly strong effect on interferon γ. This response could be beneficial in mild, but not in severe disease. Treatment options in COVID-19 could differ according to disease severity.